AN ANALYSIS OF THE ENGLISH LEARNING MODEL IN THE FINE ART EDUCATION STUDY PROGRAM UNIVERSITAS MUHAMMADIYAH MAKASSAR - Riska Febrianti As; Ismail Sangkala; Achmad Basir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Monotonous learning can make students less interested in learning.To obtain data, researcher used field note observation and interview instruments. The objects of this research are fine arts lecturer and students. The research results found that in fine arts classes lecturer used technology-based learning models and project-based learning models and perceptions revealed that most students gave positive comments regarding the learning model used in fine arts, they really liked learning English. Then technology makes it easy to collect assignments, materials and so on so they can look back if they don't understand.